2016
DOI: 10.5811/westjem.2016.6.30446
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence and Harassment Against Emergency Medicine Residents

Abstract: IntroductionSeveral studies have shown that workplace violence in the emergency department (ED) is common. Residents may be among the most vulnerable staff, as they have the least experience with these volatile encounters. The goal for this study was to quantify and describe acts of violence against emergency medicine (EM) residents by patients and visitors and to identify perceived barriers to safety.MethodsThis cross-sectional survey study queried EM residents at multiple New York City hospitals. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 16 publications
3
43
0
2
Order By: Relevance
“…There is a growing global focus on the development and retention of a healthy and sustainable healthcare workforce in low/middle-income countries (LMICs). Previous studies in the USA, Australia and LMICs report that 60.0%–87.5% of emergency healthcare providers (eg, nurses and physicians) experience some form of workplace violence (WPV) annually 1–8. WPV includes both physical and verbal assault from different perpetrators, including bystanders, patients, patients’ families and colleagues 9–11.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing global focus on the development and retention of a healthy and sustainable healthcare workforce in low/middle-income countries (LMICs). Previous studies in the USA, Australia and LMICs report that 60.0%–87.5% of emergency healthcare providers (eg, nurses and physicians) experience some form of workplace violence (WPV) annually 1–8. WPV includes both physical and verbal assault from different perpetrators, including bystanders, patients, patients’ families and colleagues 9–11.…”
Section: Introductionmentioning
confidence: 99%
“…En ambos tipos de violencia, tanto en los establecimientos públicos como en los privados, los principales agresores son los pacientes y familiares, resultados similares a lo evidenciado en múltiples otros trabajos 13,14,[31][32][33] . Cuando los pacientes reciben una atención que no cumple con sus expectativas, o perciben un trato injusto, o cuando no entienden lo que se les dice, o existe incertidumbre en sus tratamientos y pronósticos o sus vidas están en riesgo, aparecen diferentes emociones, tales como cólera, ansiedad y miedo, las que determinan el uso de palabras inadecuadas, de agresiones físicas o de provocación de episodios de violencia que involucran de alguna manera al personal sanitario, creando un ambiente de .…”
Section: Discussionunclassified
“…Physicians and staff may at times use humor, inappropriate language, or inappropriate behavior as a coping mechanism. A recent study of New York EDs found that most residents had experienced verbal harassment (97%), verbal threats (78%), and/or sexual harassment (52%) . Another recent study of 10 EM residencies found that most residents had experienced verbal abuse (86%) and verbal threats (68%) and significant numbers had experienced physical threats (50%), physical attacks (26%), sexual harassment (23%), or racial harassment (26%).…”
Section: The Ed Environmentmentioning
confidence: 99%